Public Policy Analysis in the Field of National Security: A Study on the Securitization of Illegal Asylum Seekers During the John Howard Administration in Australia - Sena Septiana; Arfin Sudirman; Yusa Djuyandi (Jurnal Public Policy, 2022)
This article aims to understand the securitisation process of MV Tampa asylum seekers during the leadership of John Howard, who tended to perceive them as a threat. As one of the countries that ratified the International Convention regarding asylum seekers, this action became a problem because it was considered a form of Australia's inconsistency towards the Convention and drew many reactions from other related parties. This article aims to discover how MV Tampa asylum seekers are framed as a national threat to Australia using the concept of Securitisation and Illegal Asylum Seekers. In this article, the author uses a qualitative method with data collection techniques through document-based studies, internet-based studies, and interviews. The author finds that the policies taken by Australia are not always state-centric because of John Howard's motives in facing the 2001 federal election. In addition, asylum seekers tend to be framed as an existential threat to social security in Australia.